2014
DOI: 10.4236/fns.2014.57073
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Properties of Meat from Grazing Podolian Young Bulls

Abstract: The effect of rearing system (pasture with supplementation 15% crude protein OUT15 vs indoor IND) on meat nutritional and nutraceutical properties was evaluated in twenty Podolian young bulls. Meat quality characteristics were measured on three different muscles (Longissimus dorsi, LD, Semimembranosus, SM, Semitendinosus, ST), vacuum-packaged and chilled stored at 2˚C -4˚C for 15 days. No differences were found on chemical composition in meat from animals reared with different rearing system. Pasture with supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In this study, Podolian meat showed a greater MUFA concentration, while no differences between breeds were detected for the SFA and PUFA contents. The results observed in this study for the fatty acid profile of Podolian meat are quite similar to those reported in the literature [19,24,43]. There is general agreement on the fact that the genotype is the major source of variation in meat fatty acid composition [58].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, Podolian meat showed a greater MUFA concentration, while no differences between breeds were detected for the SFA and PUFA contents. The results observed in this study for the fatty acid profile of Podolian meat are quite similar to those reported in the literature [19,24,43]. There is general agreement on the fact that the genotype is the major source of variation in meat fatty acid composition [58].…”
Section: Discussionsupporting
confidence: 90%
“…So far, few literature works are available on the productive performances and meat quality traits of Katerini cattle [15], while several studies have been carried out on Podolian cattle farmed in southern Italian regions, such as Basilicata [19,20,43] and Apulia [5,21,24], under different farming systems. In our study, the slaughtering weight was generally lower as compared to the findings reported by other authors for young bulls slaughtered at the same age, which received feed supplementation in addition to grazing during the finishing period, while the dressing percentage was quite similar [5,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation